Blue Rubber Bleb Nevus Syndrome: A Case Report (Bangladesh Journal of Child Health, 2018)
Blue rubber bleb nevus syndrome (BRBNS) is a rare condition that is characterized by malformations of the venous system that significantly involve the skin and viscera.Cutaneous malformations are usually asymptomatic and do not require treatment except cosmetic purpose. The treatment of gastrointestinal lesions is determined by the extent of involvement and severity of the disease.We are presenting a case of BRBNS who was admitted in the paediatric ward of Bangabandhu Sheikh Mujib Medical University(BSMMU) with the complaints of progressive pallor since one year of age, passage of blackish stool for last two years, presence of soft bluish/and swelling all over the body and multiple dark blue to blackish nodule present in palm and sole. She got blood transfusion over one hundred (100) times. Endoscopy showed multiple haemangioma with active bleeding in upper GIT. After possible investigations she was diagnosed as a case of BRBNS and treated with available treatment facility.Bangladesh J Child Health 2017; VOL 41 (2) :125-128